Indigenous school education and traditional knowledge: The perception of Pipipã de Kambixuru teachers - Ana Carolina Gomes Coimbra; Maria Luisa Branco (Arizona State University, 2020)
This article is part of a doctoral research that deals with the school education and traditional knowledge of Pipipã de Kambixuru, located in the municipality of Floresta, Pernambuco, Brazil. The reports of the indigenous teachers will be presented on the importance of school education and the inclusion of traditional knowledge, namely medicine, Toré and Jurema Sagrada in the differentiated curriculum of the Joaquim Roseno Indigenous State School in the Travessão do Ouro Village. An ethnographic approach was followed, materializing in a participant observation in the indigenous territory, where interviews were made with the teachers, emphasizing the intercultural process of the curriculum construction and methodologies used in the classes. Traditional knowledge is presented to the community at school and through orality and, despite existing acculturation processes, the indigenous community perseveres in maintaining its legacy. Intercultural discourse contributes to the permanence and resistance of this people, since the cultural diversity in its epistemological concepts and in its practice is of great relevance both for academic construction and for a pedagogy of life.